Corporate branding and consumers - Theo Araujo, ....- (Amsterdam : SWOCC, 2017)
It is often said that the relevance of corporate branding will only increase in the coming years, given the increasingly competitive environment has become due to the rise of social media, the fragmented media landscape and overall societal concerns and expectations regarding trust, credibility and transparency, this book updates our knowledge about how corporate branding can be relevant to and influence consumers.